2014
DOI: 10.1088/1009-0630/16/2/03
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectroscopic Investigation of Ar/CH3OH and Ar/N2/CH3OH Atmospheric Pressure Plasma Jets

Abstract: Ar/CH3OH and Ar/N2/CH3OH plasma jets were generated at atmospheric pressure by dual-frequency excitations. Two different cases were studied with focus laid on the generation of CN radicals. In one case Ar gas passed through a bubbler with saturated methanol steam but without addition of N2 (Ar/CH3OH plasma). In the other case N2 passed through the bubbler with saturated methanol steam (Ar/N2/CH3OH plasma). The optical emission lines of CN radicals have been observed in these two cases of plasma discharges. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Figure 5 illustrates the variation of C (247.8 nm)/C 2 (516.4 nm), CN (388.3 nm)/C 2 (516.4 nm) and CH (431.3 nm)/C 2 (516.4 nm) emission intensity ratios as a function of the ethanol content from 0 to 4600 ppm. These ratios are much lower than that in [42]. These three curves have the similar variation tendency, gradually decreasing with the ethanol content increase, which indicated that the higher ethanol content is inclined to create the C 2 radicals.…”
Section: P -Pmentioning
confidence: 72%
See 3 more Smart Citations
“…Figure 5 illustrates the variation of C (247.8 nm)/C 2 (516.4 nm), CN (388.3 nm)/C 2 (516.4 nm) and CH (431.3 nm)/C 2 (516.4 nm) emission intensity ratios as a function of the ethanol content from 0 to 4600 ppm. These ratios are much lower than that in [42]. These three curves have the similar variation tendency, gradually decreasing with the ethanol content increase, which indicated that the higher ethanol content is inclined to create the C 2 radicals.…”
Section: P -Pmentioning
confidence: 72%
“…The electron energy decays as the ethanol content increases due to the electron impact processes to ethanol molecules and their fragments. In [42], we had studied the OES of the same carbonaceous radicals with the similar hydrocarbon (methanol, CH 3 OH) and obtained the similar results. However, the RF excitation frequency (33 MHz) in this paper is much higher than that in [42] (2 MHz).…”
Section: P -Pmentioning
confidence: 74%
See 2 more Smart Citations
“…The main argon flow is fed into the quartz syringe with a constant flow rate of 1 slm (standard liters per minute) in every experiment. The TEOS content carried into the discharge region is calculated using Antoine equation [5]. The micro-plasma jet is directed toward a substrate which fixed at 2 mm apart from the quartz syringe nozzle.…”
Section: Methodsmentioning
confidence: 99%